Identification of cocoa (Theobroma cacao L.) genetic uniformity through RAPD molecular markers. - Helia Dewi, Nur Afni; Pancaningtyas, Sulistyani; Su’udi, Mukhamad (Indonesian Coffee and Cocoa Research Institute, 2023)
Theobroma cacao L. has been propagated through either generative or vegetative techniques. One of the vegetative methods of propagating cocoa is somatic embryogenesis. Somatic embryogenesis has been employed by the Indonesian Coffee and Cocoa Research Institute for producing cocoa seedlings. Plant breeding activities are hampered by the significant level of plant heterogeneity among their progeny. Mislabelling of genetic impurities can be an issue. Molecular markers can be used to detect genetic variation at an early stage. The most common marker is the RAPD molecular marker. The study aims to determine the polymorphic RAPD primers in the analysis of genetic uniformity between mother plants and the seedlings derived from somatic embryogenesis (SE). The analyzed samples consisted of twelve individuals: six mother plants and six seedlings derived from SE. The results revealed that the percentage of polymorphic bands was 100% with band sizes ranging from 295-2785 bp for primer GY169 while for primer GY107 percentage of polymorphic bands was 80% with band sizes ranging from 345-1678 bp. Primer GY169 and primer GY107 can be amplified and used for cocoa similarity and heterogeneity.